Incorporating Popular Culture Elements into Hanan Attaki’s Dakwah - Rahayu, Mundi; Santi, Vita Nur; Munjiah, Ma'rifatul; Anshory, Abdul Muntaqim Al (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
The current research aims at exploring the use of popular culture in the preaching (or Dakwah, in popular Indonesian term) delivered by Ustadz Hanan Attaki. As one of the most popular Islamic preachers in Indonesia, Ustadz Hanan Attaki applies the elements of popular culture, such as slang languages, English terms, music, and youth fashion, to deliver the Islamic teaching. The ways of applying the preaching with popular culture, is considered as relevant and appealing for the youths. Through the qualitative approach, the current research analyzes Ustadz Hanan Attaki’s preaching through the Fairclough’s critical discourse analysis, to get the ideas of how the popular culture is integrated into his preaching. The result shows that the use of popular culture does not only increase the preaching, but it also strengthens the audience’ understanding of Islamic values through the terms that are familiar to the young people. The strategy also attracts the emotional bond between the preacher and the audience so that the religious messages is accepted and comprehended. The reference of popular culture is sometimes also problematic as it is basically in the different discourse. The current research concluded that the integration of popular culture in religious preaching is effective strategy for a preaching which is contextual, although it is necessary to be careful so that it does not blur or make the religious teaching biased. الملخص يهدف البحث الحالي إلى استكشاف استخدام الثقافة الشعبية في الوعظ الذي ألقاه الأستاذ حنان أتكي. باعتباره أحد الدعاة الإسلاميين الأكثر شعبية في إندونيسيا، يطبق الأستاذ حنان أتاكي عناصر الثقافة الشعبية، مثل اللغات العامية والمصطلحات الإنجليزية والموسيقى وأزياء الشباب، لتوصيل التعاليم الإسلامية. تعتبر طرق تطبيق الوعظ مع الثقافة الشعبية ذات صلة وجذابة للشباب. ومن خلال المنهج النوعي، يحلل البحث الحالي وعظ الأستاذ حنان أتاكي من خلال تحليل الخطاب النقدي لفيركلاف، للحصول على أفكار حول كيفية دمج الثقافة الشعبية في وعظه. وتظهر النتيجة أن استخدام الثقافة الشعبية لا يؤدي إلى زيادة الوعظ فحسب، بل يعزز أيضًا فهم الجمهور للقيم الإسلامية من خلال المصطلحات المألوفة لدى الشباب. كما تعمل الاستراتيجية على جذب الرابط العاطفي بين الداعية والجمهور بحيث يتم قبول الرسائل الدينية وفهمها. في بعض الأحيان تكون الإشارة إلى الثقافة الشعبية مشكلة أيضًا لأنها موجودة بشكل أساسي في الخطاب المختلف. وخلصت الدراسة الحالية إلى أن دمج الثقافة الشعبية في الوعظ الديني هو استراتيجية فعالة للوعظ السياقي، على الرغم من أنه من الضروري توخي الحذر حتى لا يؤدي إلى طمس أو جعل التعاليم الدينية متحيزة Abstrak Penelitian kali ini bertujuan untuk mengeksplorasi pemanfaatan budaya populer dalam dakwah yang disampaikan oleh Ustadz Hanan Attaki. Sebagai salah satu pendakwah Islam terpopuler di Indonesia, Ustadz Hanan Attaki menerapkan unsur-unsur budaya populer, seperti bahasa gaul, istilah Inggris, musik, dan fashion anak muda, dalam menyampaikan ajaran Islam. Penerapan dakwah dengan budaya populer, ini sangat relevan dan menarik bagi generasi muda. Dengan pendekatan kualitatif, penelitian kali ini menganalisis dakwah Ustadz Hanan Attaki melalui analisis wacana kritis Fairclough, untuk mendapatkan gambaran bagaimana budaya populer diintegrasikan ke dalam dakwahnya. Hasil penelitian menunjukkan bahwa penggunaan budaya populer tidak hanya meningkatkan dakwah, tetapi juga memperkuat pemahaman jamaah terhadap nilai-nilai Islam melalui istilah-istilah yang akrab di telinga generasi muda. Strategi tersebut juga menarik ikatan emosional antara penceramah dan pendengarnya sehingga pesan-pesan keagamaan dapat diterima dan dipahami. Referensi budaya populer terkadang juga bermasalah karena pada dasarnya keduanya berbeda wacana. Penelitian yang dilakukan saat ini menyimpulkan bahwa integrasi budaya populer dalam dakwah keagamaan merupakan strategi yang efektif untuk dakwah yang bersifat kontekstual, namun perlu kehati-hatian agar tidak mengaburkan atau menjadikan ajaran agama menjadi bias.